Peningkatan Keterampilan Berpikir Kritis Melalui Ekstrakurikuler Empat Pilar Kebangsaan di SMA Negeri 1 Tanah Abang (PALI) - Saputra, Dimansyah; El Faisal, Emil (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
Critical thinking skills are essential competencies in 21st-century learning, yet national assessment results indicate most students have not optimally developed these skills. This study aims to analyze the improvement of students' critical thinking skills through the Four Pillars of Nationhood extracurricular activities at SMA Negeri 1 Tanah Abang. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with the supervising teacher and vice principal for student affairs, non-participant observations of extracurricular activities, and documentation. The findings reveal that the Four Pillars of Nationhood extracurricular activities successfully enhance six indicators of critical thinking skills interpretation through contextual problem identification, analysis through discussion of cause-effect relationships, inference through discussion conclusions, evaluation through reflection and one day one hour program, explanation through student presentations, and self-regulation through memorization progress recording. The learning strategies implemented include using current issues, interactive discussions, peer review of opinions, and literacy assignments. Observation results show strategy implementation achieved a score of 90 percent in the excellent category. The Four Pillars of Nationhood extracurricular activities proved effective as an alternative platform for optimizing critical thinking skills through structured, systematic, and contextual non-formal learning.